Pelatihan Dan Pengembangan Berbasis Digital: Implementasi Pembelajaran Daring, Platform Pelatihan Interaktif, Dan Teknologi Simulasi Dalam Pengembangan Karyawan - Laurentin Carolin Tiara; Herlyta Ryzki Lestari; Cintya Dwi Nur Kholifah; Reynald Fakhrul Fakhriza Zulfi; Mochammad Isa Anshori (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
A good leader will pay attention to the quality of his employees' performance. This statement illustrates the need for leaders to be sensitive in managing Human Resources (HR) wisely. Wise Human Resources (HR) management can be implemented by holding digital-based employee training and development with the hope that employee training and development can increase employee knowledge, development and skills without disrupting working hours. The presence of digital-based training and development will improve the quality of employees so they are able to compete with employees of other companies which will influence the progress of the company's performance and development. This digital-based training and development can be carried out through various digital platforms and applications that are accessible to employees.